2013
DOI: 10.1016/j.febslet.2013.06.023
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐133b stimulates ovarian estradiol synthesis by targeting Foxl2

Abstract: Edited by Laszlo NagyKeywords: Granulosa cell miR-133b Foxl2 StAR CYP19A1 Estrogen a b s t r a c t Forkhead L2 (Foxl2) is expressed in ovarian granulosa cells and participates in steroidogenesis by transcriptionally regulating target genes such as steroidogenic acute regulatory protein (StAR) and CYP19A1. In this study, a direct link between microRNA-133b (miR-133b) and Foxl2-mediated estradiol release in granulosa cells was established. miR-133b was involved in follicle-stimulating hormone (FSH)-induced estro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 42 publications
(61 reference statements)
2
79
0
1
Order By: Relevance
“…As it has been previously reported that miR-133b acts as a tumor suppressor in lung cancer, the expression levels of miR-133b in A549 cells were measured following radiation treatment (13)(14)(15)(16)(17)(18). The expression of miR-133b was significantly reduced following radiation treatments of 0.2 to 0.6 Gy (Fig.…”
Section: Mir-133b Is Negatively Correlated With Radioresistancementioning
confidence: 57%
See 1 more Smart Citation
“…As it has been previously reported that miR-133b acts as a tumor suppressor in lung cancer, the expression levels of miR-133b in A549 cells were measured following radiation treatment (13)(14)(15)(16)(17)(18). The expression of miR-133b was significantly reduced following radiation treatments of 0.2 to 0.6 Gy (Fig.…”
Section: Mir-133b Is Negatively Correlated With Radioresistancementioning
confidence: 57%
“…Discussion miR-133b has been reported as a tumor suppressor functioning in numerous types of cancer that demonstrate low miR-133b expression, as noted in colorectal (13), gastric (14), bladder (15), lung (16), esophageal (17), ovarian (18) and breast (19) cancer. However, the role of miR-133b within radiosensitivity remains under investigation.…”
mentioning
confidence: 91%
“…Moreover, physiological changes in the expression of miRNAs supporting putative roles during follicle development have often not been demonstrated , Yang et al 2012, Dai et al 2013, and detailed spatiotemporal miRNA profiles during development are not available. In a previous study (McBride et al 2012), we used sequencing to characterize the developmental changes in miRNA expression in ovine follicles, although our focus was on terminal differentiation (follicle-luteal transition) rather than on follicle growth and atresia.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already reported effects of specific miRNAs on different aspects of granulosa cell function , including steroidogenesis (Yao et al 2010, Xu et al 2011, Yin et al 2012, Dai et al 2013, proliferation (Yao et al 2010, Yan et al 2012, Dai et al 2013, survival (Carletti et al 2010, Yang et al 2012, terminal differentiation (Kitahara et al 2013), and cumulus expansion (Yao et al 2014). With a few exceptions (Carletti et al 2010, Kitahara et al 2013, most evidence on follicular roles of miRNAs has been obtained using cultured cells, particularly rodent cells, and in some cases actual changes in the expression of these miRNAs during follicle development have not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Another miR shown to modulate estrogen synthesis is miR-133b, which increases estrogen synthesis in the ovaries by targeting Foxl2, a negative regulator of the steroidogenic enzymes, STAR protein and CYP19A1. miR-133b was shown to associate with FOXL2 3 0 -UTR, reducing FOXL2 protein levels, and its binding to STAR and CYP19A1 promoter sequences in granulosa cells, thereby increasing estrogen synthesis and secretion (Dai et al 2013). It is likely that further miRs will emerge as regulating hormone synthesis enzymes, and given the clinical importance of intratumoural steroid synthesis for both breast and prostate cancer it will be of major interest to determine whether these are disregulated in both tumour types and whether they are regulated by steroid signalling themselves.…”
Section: Estrogen Modulation Of Mir Biogenesismentioning
confidence: 99%